Formation and evolution of the unexpected PbI2 phase at the interface during the growth of evaporated perovskite films. Issue 27 (27th June 2016) - Xu, Haitao; Wu, Yanglin; Cui, Jian; Ni, Chaowei; Xu, Fuzong; Cai, Jiang; Hong, Feng; Fang, Zebo; Wang, Wenzhen; Zhu, Jiabin; Wang, Linjun; Xu, Run; et al.
Abstract : A PbI2 phase is found to be inevitably formed at the interface in dual-source evaporated perovskite films that will block carrier transport. Abstract : The interface chemistry and evolution of the evaporated perovskite films on ITO, pedot/ITO, Si and glass substrates are studied. As evidenced by X-ray diffraction and X-ray photoemission spectroscopy (XPS) results, the PbI2 phase is found to be inevitably formed at the very initial growth stage, even under the conditions of a MAI-rich environment. The extremely low binding energy of adsorbed MAI particles on all the above substrates, as compared to that of PbI2 particles, is responsible for the presence of the PbI2 phase at the interface. The formation of both hole and electron barriers at the interface of PbI2 /MAPbI3, as evidenced by XPS measurements, could block carrier transport into the electrode and thus deteriorate solar cell performance. This result reveals the origin of the poor performance of perovskite solar cells (PSCs) by the vacuum evaporation method, and may help to improve the performance of PSCs made using the vacuum evaporation method.